2023
DOI: 10.1002/aoc.6968
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and genotoxicity of green synthesized silver, gold, and silver/gold bimetallic NPs on BHK‐21 cells and human blood lymphocytes using MTT and comet assay

Abstract: In cancer therapy, nanoparticles (NPs) shall be applied possibly by inoculation in the veins of humans. This action will connect them with white blood cells (WBCs) and red blood cells (RBCs) in the bloodstream before they reach their main targeted cancer cells. However, possible cytotoxicity and genotoxic effects of silver, gold, and silver/gold bimetallic NPs (Ag, Au, and Ag/Au BNPs) on baby hamster kidney-21 (BHK-21) cells and human blood lymphocytes were studied here by comet and MTT assays. Here, Ag, Au, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…[54] The present FTIR analysis report is justified by the previous results. [55] These results are also in correlation with the previous study. [56,57] The XRD peaks in the present study reported four brag reflections of BNPs.…”
Section: Discussionsupporting
confidence: 92%
“…[54] The present FTIR analysis report is justified by the previous results. [55] These results are also in correlation with the previous study. [56,57] The XRD peaks in the present study reported four brag reflections of BNPs.…”
Section: Discussionsupporting
confidence: 92%
“…Sher and Ahmed et al, Wang et al, and Sher and Alkhalifa et al [90][91][92] reported that NPs exhibited anti-AChE activity by adsorption or interaction with the enzyme. According to Sher and Ahmed et al and Rajakumar et al, 89,93 because of the NPs' lipophilicity and enzyme molecules' hydrophobicity, the NPs exhibited attraction to the AChE enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…[92] A perusal of scientific studies reports that carboxylic acids, terpenoids, aldehydes, flavonoids, amides, and ketones are the vital bio-molecules accountable for efficient metallic reduction for interpreting its applicative properties. [93] The IR spectra of HP-AgNPs with the slight changes in peaks credited to interaction between functional moieties present in HPE and AgNPs. Thus, from the FTIR spectrum, it may be assumed that these phyto-components are responsible the bioreduction as well as in the stabilization of HP-AgNPs.…”
Section: Discussionmentioning
confidence: 99%